Mohawk - Salmon River School District, Ft. Covington, NY.; Salmon River School District, Ft. Covington, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
This is a highly illustrated text designed to teach vocabulary of Akwesasne Mohawk at the elementary level in a bilingual/bicultural setting. Each word is accompanied by its English equivalent. Vocabulary includes numbers 1-5, common animals and substances, and every day expressions such as "hello""goodbye," and "thank you." The Mohawk spelling and pronunciation are those used by the Akwesasne Mohawk people. Some basic dialogue exchanges are included at the end. The book is one of a series produced by the Title IV bilingual/bicultural program at the Salmon River Central School in New York State. (CLK)
Sponsoring Agency: New York State Education Dept., Albany. Office of Cultural Education.
ERIC Note: For related document, see FL 007 085.
Educational level discussed: Elementary Education.
Microfiche.
Keywords: American Indian Languages; Biculturalism; Bilingual Education; Bilingualism; Elementary Education; Instructional Materials; Pronunciation Instruction; Reading Instruction; Reading Materials; Textbooks; Uncommonly Taught Languages; Vocabulary Development; Akwesasne Mohawk (Tribe); Books